Lessons learnt from the implementation of new models of care delivery through alliance governance in the Southern health region of New Zealand: a qualitative study - Gurung, Gagan; Jaye, Chrystal; Gauld, Robin; Stokes, Tim (BMJ open, 2022)
ObjectivesTo explore the process of implementation of the primary and community care strategy (new models of care delivery) through alliance governance in the Southern health region of New Zealand (NZ).DesignQualitative semistructured interviews were undertaken. A framework-guided rapid analysis was conducted, informed by implementation science theory—the Consolidated Framework for Implementation Research.SettingSouthern health region of NZ (Otago and Southland).ParticipantsEleven key informants (Alliance Leadership Team members and senior health professionals) who were involved in the development and/or implementation of the strategy.ResultsThe large number of strategy action plans and interdependencies of activities made implementation of the strategy complex. In the inner setting, communication and relationships between individuals and organisations were identified as an important factor for joint and integrated working. Key elements of a positive implementation climate were not adequately addressed to better align the interests of health providers, and there were multiple competing priorities for the project leaders. A perceived low level of commitment from the leadership of both organisations to joint working and resourcing indicated poor organisational readiness. Gaps in the implementation process included no detailed implementation plan (reflected in poor execution), ambitious targets, the lack of a clear performance measurement framework and an inadequate feedback mechanism.ConclusionsThis study identified factors for the successful implementation of the PCSS using an alliancing approach in Southern NZ. A key enabler is the presence of a stable and committed senior leadership team working through high trust relationships and open communication across all partner organisations. With alliances, partnerships and networks increasingly held up as models for integration, this evaluation identifies important lessons for policy makers, managers and services providers both in NZ and internationally.